Unveiling the power behind the curtain: The influence of political wives of local chief executives in the Philippines - Pamposa, Angel; Nitafan, Rowell P. (Faculty of Social and Political Science, Universitas Airlangga, 2025)
For centuries, the role of political spouses has been a crucial, though often overlooked, facet of political life. While scholarly and public attention predominantly fixates on the politician, the contributions of their partners have played a significant role in shaping and influencing the political landscape, a dynamic frequently underexplored in political discourse. To explicate the phenomenon, the study was conducted to explore the role of political spouses in the political landscape of the country, particularly the power of wives of local chief executives (LCEs) in local governance. The study is qualitative research that employed case study design to examine the scope of influence and extent of control of the first ladies of municipal and city mayors in Mindanao during the 2022-2025 term of office—an area of public leadership that remains largely understudied within mainstream political analysis. The study revealed both shared and diverse views and insights among political wives in balancing their roles as mothers and spouses of local chief executives. Across participants, they regarded their roles as demanding yet rewarding, requiring adaptability, strong support networks, and effective time management. They consistently acted as informal advisors, influencing policy and advocacy efforts through their proximity to power. Their accounts highlighted active engagement in community development and navigating public and private responsibilities. While their perspectives were broadly similar, individual journeys differed based on strategies employed to manage these dual demands.